Improving the freight transport of a developing economy: A case of Boankra inland port - Richmond Kwesi Ansah; Kwabena Obiri Yeboah; Grace Akipelu (Journal of Shipping and Trade (JST), 2020)
Purpose Shippers and Freight Forwarding Agents spend much time clearing their cargo from the Ghanaian ports. As a result, the cost of doing business in Ghana through the Tema and Takoradi ports is high. This research investigates the potential impact the establishment of an inland port will have on a reduction in congestion at the Tema and Takoradi ports and on the efficiency of the freight transport system. Methodology/approach This study used questionnaires to gather data through an experience survey conducted at the Ghana Sea Ports and Boankra inland port. Findings The study found out that for the inland Port to work effectively, there should be a connection from the Boankra inland port to the Takoradi and Tema Sea Ports as well as the container depots of the neighboring landlocked Sub-Saharan African Countries.. The study discovered that the implementation of the Boankra inland port will result in the decongestion and efficiency of Ghanaian seaports. Factors such as the increase in skills and experience of personnel; the use of management information systems; formulation of programmes and policies in decongesting the two main Ghanaian seaports; enhanced road network; adaptation of new technologies in the cargo handling process; and reduced bureaucracy in clearing processes at the ports are arbitrating factors through which the establishment of the Boankra inland port may have an impact on the seaports and the Freight transport industry at large. It was found that the challenges which may impede the improvement of freight transport in Ghana are inefficiencies and distortions in the trading system; unnecessary bureaucratic clearing processes; weak regulatory framework; Poor quality control;, inadequate staff; political interference, and lack of capital. It was found that for the Boankra Inland Port to be efficient, the officials and stakeholders must be trained; the various institutions in the transport chain must be empowered; corruption among port officials must be managed; there must be minimal political interference in the port operations; there must be more investment into the freight transport system; and there must be trade regulations to govern the freight transport system. Originality This novel study differentiates itself from existing studies on Port System by focusing on inland ports in Africa and their influence on the efficiency and decongestion of seaports.
Keywords: 650; Regionalization; Boankra inland port; Congestion; Port efficiency